Bibliometric visual analysis of the poly(vinylidene fluoride–trifluoroethylene) piezoelectric nanomaterial: research history, hotspots, and developmental trend - Chen, Zhiguang; He, Wen; Zhang, Wei (Frontiers in Materials, 2023)
Poly(vinylidene fluoride trifluoroethylene) (P(VDF-TrFE)) is stands out as an organic polymer that with exhibits excellentremarkable piezoelectric properties; , it coupled withis highly chemically stability and biocompatibility,e, biocompatible, and is considered to berendering it the most promising organic piezoelectric nanomaterial.To comprehensively review the All relevant results pertinent literature on poly(vinylidene fluoride trifluoroethylene) or P (VDF-TrFE) in English between from1992 and to 2022, were retrieved fromwe utilized the Web of Science Core Collection., Additionally, the bibliometric tools including such as CiteSpace, VOSviewer, Bibliometrics online analysis platforms (https://bibliometric.com), along with and SCImage graphics, were used employed to identify thedelineate historical features, track the evolution of active topics, and identify emerging trends on the P(VDF-TrFE) field. The number of annual publicationshed and cited citation counts for articles on P(VDF-TrFE) increased annuallyhave exhibited consistent growth since 1992, with Asia, particularly notably China, having published the most articles related tocontributing the highest number of publications on P(VDF-TrFE) materials. HoweverInterestingly, researchers in the USA demonstrated the were found to cooperate most stronglyrobust international collaborations across various with a variety of countries. Keywords were divided categorized into nine clusters: 0# vinylidene fluoride, 1# thin film transient, 2# energy harvesting, 3# dielectric property, 4# thin film, 5# film, 6# mobile modeling, 7# growth, and 8# pyroelectric sensor. The performance of constituent materials in electronic energy-storage applications as well as current and future research in nano fields, including nanofilms, nanofibers, and nanogenerator, are hotspots and developmental trends. Among the most cited articles, This is a provisional file, not the final typeset article these articles are commonly related to PVDF and P(VDF-TrFE) ferroelectricity.Therefore, we believe that the electromechanical coupling performance of P(VDF-TrFE) and the research in nano fields is research hotspot that will trend into the future.